Pancreatectomy for chronic pancreatitis. - Frey, C F (1976)
Of one hundred and forty-nine patients (101 male and 48 female) 4-67 years of age, 117 were alcoholics and underwent pancreatectomy because of episodic or continuous abdominal pain or complications or chronic pancreatitis. Nineteen patients underwent pancreaticoduodenectomy, seventy-seven 80-95% distal resection, anf fifty-three 40-80% distal pancreatic resection. There were 3 operative death and 30 late deaths 6 months to 11 years post pancreatectomy. Twenty-one patients were lost to followup, 1 to 11 years post pancreatectomy. Ninety-five patients are known to be alive, 4 of whom are institutionalized. Indications for pancreatectomy in addition to abdominal pain include recurrent or multiple pseudocysts, failure to relieve pain after decompression of a pseudocyst, pseudoaneurysm of the visceral arteries associated with a pseudocyst, recurrent attacks of pancreatitis unrelived by non-resective operations, duodenal stenosis and left side portal hypertension. The choice between pancreaticoduodenectomy or distal resection of 40-80% or 80-95% of the pancreas should be based on the principle site of inflammation whether proximal or distal in the gland, the size of the common bile duct, the ability to rule out carcinoma, and the anticipated deficits in exocrine and endocrine function. The risk of diabetes is very significant after 80-95% distal resection and of steatorrhea after pancreaticoduodenectomy. When the disease process can be encompassed by 40-80% distal pancreatectomy this is the procedure of choice.